112k views
1 vote
3(x – 2) + 4x = 10(x + 1)

2 Answers

5 votes

Answer:

x=-16/3 (-5.33)

Explanation:

3(x-2)+4x=10(x+1)

3x-6+4x=10x+10

7x-6=10x+10

-6-10=10x-7x

-16=3x

x=-16/3

User Schumacherj
by
4.9k points
2 votes

Answer:
x=-(16)/(3)

Explanation:

Given the equation
3(x - 2) + 4x = 10(x+ 1), you need to solve for the variable "x":

Apply Distributive property:


3x - 6 + 4x = 10x +10

Add the like terms:


7x - 6= 10x+10

Subtract 10 to both sides of the equation:


7x - 6-10= 10x +10-10\\\\7x-16=10x

Subtract
7x from both sides:


7x-16-7x=10x-7x\\\\-16=3x

And finally divide both sides by 3:


(-16)/(3)=(3x)/(3)\\\\x=-(16)/(3)

User Akida
by
4.9k points